Preparation method of TOPcon battery
By forming the first groove during the preparation of the TOPcon battery and using laser-assisted sintering method, the problem of difficulty in simultaneously increasing the open circuit voltage and filling factor in the prior art is solved, and more efficient battery performance is achieved.
Patent Information
- Application Number
- CN202411550430.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The existing TOPcon battery preparation methods are difficult to maintain or increase the filling factor while increasing the open circuit voltage, resulting in limited battery efficiency.
By forming a first groove on the first side of the substrate, the metal paste is printed and heated and sintered, so that the metal paste is made to form ohmic contact with the doping layer through the passivation layer. In addition, laser-assisted sintering is used to perform secondary sintering to enhance the ohmic contact effect of the metal paste with the passivation layer and the polysilicon layer.
When the sintering temperature is reduced, the filling factor of the battery is maintained or increased, thereby improving the efficiency of the battery, and avoiding the problem that metal paste is difficult to pass through the anti-reflection layer and the passivation layer.
Smart Images

Figure CN119451275A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of solar cells, and specifically provides a method for preparing a TOPcon cell. Background Art
[0002] At present, with the continuous consumption of traditional energy, energy issues have become an important issue of global concern, and promoting the development of renewable energy has become the focus. Among them, solar energy has significant advantages such as cleanliness, safety, and abundant resources. It has gradually emerged and become the focus of research and development. After decades of development, photovoltaic power generation technology has also made remarkable progress.
[0003] Among them, TOPcon battery is a kind of solar cell. The efficiency of the battery has exceeded 26%, and it has not yet reached the limit. The efficiency of TOPcon battery (for example, in terms of improving the open circuit voltage and fill factor of the battery) still has huge room for improvement. Among them, the fill factor is the ratio of the product of the current and voltage when the battery has maximum output power to the product of the short-circuit current and open circuit voltage. The physical meaning of the fill factor is the uniformity of the electric field strength in the solar cell, which can also be understood as the magnitude of the resistance to the movement of electrons in the solar cell. The higher the fill factor, the smoother the flow of electrons in the battery, and the more solar energy can be fully converted into electrical energy; conversely, the lower the fill factor, the more resistance there is to the flow of electrons inside the solar cell, and it is impossible to fully utilize solar energy to convert into electrical energy. Therefore, the fill factor can provide the actual performance of the output current and voltage of the solar cell, as well as the conversion efficiency of the solar cell.
[0004] The TOPcon cell includes a substrate, on the first side of which the emitter of the doped layer is formed by boron expansion, and then a passivation layer and an anti-reflection layer are formed in sequence on the side of the doped layer away from the substrate. Subsequently, a metal paste is printed on the anti-reflection layer, and then sintered at high temperature. During the sintering process, the metal paste corrodes the anti-reflection layer and the passivation layer to form an ohmic contact with the doped layer. The better the ohmic contact effect between the metal paste and the doped layer, the higher the fill factor.
[0005] At present, when the metal paste is sintered at high temperature, the open circuit voltage of the battery can be increased by lowering the sintering temperature. However, after the sintering temperature is lowered, the corrosion rate of the metal paste on the anti-reflection layer and the passivation layer is reduced, which can easily lead to the difficulty of the metal paste to pass through the anti-reflection layer and the passivation layer, or the contact point between the metal paste and the doping layer after passing through the anti-reflection layer and the passivation layer is uneven, affecting the ohmic contact effect between the metal paste and the doping layer, and ultimately making it difficult to improve the fill factor of the battery, affecting the battery efficiency. Summary of the invention
[0006] The present disclosure aims to solve the above-mentioned technical problem, that is, to solve the problem that the existing preparation method of TOPcon battery is difficult to maintain or improve the fill factor while improving the open circuit voltage.
[0007] In a first aspect, the present disclosure provides a method for preparing a TOPcon battery, comprising: providing a battery substrate, the battery substrate comprising a substrate and a doping layer, a passivation layer and a first anti-reflection layer sequentially formed on a first side of the substrate; forming a first groove, the first groove extending from the surface of the first anti-reflection layer to the first anti-reflection layer or the passivation layer; printing metal paste in the first groove; heating and sintering the metal paste so that the metal paste passes through the passivation layer and forms an ohmic contact with the doping layer.
[0008] In a specific embodiment of the method for preparing the TOPcon battery, the first groove extends into the passivation layer, and the thickness of the passivation layer region exposed by the first groove is 1 nm to 2.5 nm.
[0009] In a specific embodiment of the above-mentioned method for preparing the TOPcon battery, the temperature of the heating and sintering is 600°C to 700°C.
[0010] In a specific embodiment of the preparation method of the above-mentioned TOPcon battery, the metal slurry is silver paste, and the weight percentage of the silver paste is: 90% to 95% silver powder, 0.2% to 0.3% glass powder, 1% to 3% organic carrier and 0% to 1% inorganic additive.
[0011] In a specific embodiment of the preparation method of the above-mentioned TOPcon battery, the preparation method further comprises: after heating and sintering the metal slurry, performing secondary sintering on the metal slurry, and the secondary sintering adopts laser-assisted sintering.
[0012] In a specific embodiment of the preparation method of the above-mentioned TOPcon battery, the laser-assisted sintering includes: applying a bias voltage of 10V to 40V between the metal slurry and the second side of the substrate; the wavelength of the scanning laser is 500nm to 1200nm, the scanning speed is 30nm / s to 100mm / s, and the scanning time is 0.5s to 1s.
[0013] In a specific embodiment of the method for preparing the TOPcon battery, the thickness of the passivation layer is 4 nm to 6.5 nm.
[0014] In a specific embodiment of the method for preparing the TOPcon cell, the thickness of the first anti-reflection layer is 70 nm to 100 nm.
[0015] In a specific embodiment of the method for preparing the TOPcon cell, the method further comprises: sequentially forming a tunneling oxide layer, a polysilicon layer and a second anti-reflection layer on the second side of the substrate.
[0016] In a specific implementation of the method for preparing the TOPcon battery, the method further comprises: before forming the doping layer, texturing the first side of the substrate.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] The preparation method of the TOPcon battery provided by the present disclosure includes: providing a battery substrate, the battery substrate includes a substrate and a doping layer, a passivation layer and a first anti-reflection layer formed in sequence on the first side of the substrate; forming a first groove, the first groove extending from the surface of the first anti-reflection layer to the first anti-reflection layer or the passivation layer; printing a metal paste in the first groove; heating and sintering the metal paste so that the paste passes through the passivation layer and forms an ohmic contact with the doping layer. By opening the first groove, the thickness of the passivation layer corroded by the metal paste during the heating and sintering process can be reduced, thereby ensuring that when the sintering temperature is reduced, the metal paste in the first groove can also corrode the remaining passivation layer, thereby forming a good ohmic contact with the doping layer, thereby maintaining the filling factor of the battery.
[0019] Furthermore, printing a low-corrosive silver paste on the first side of the substrate helps control the corrosion rate of the silver paste on the passivation layer and reduces the possibility of the silver paste corroding through the passivation layer and contacting the substrate.
[0020] Furthermore, after the metal slurry is heated and sintered, the metal slurry is subjected to laser-assisted sintering to improve the ohmic contact effect between the metal slurry and the passivation layer without causing the battery to lose open-circuit voltage, thereby improving the battery's fill factor and achieving the purpose of improving battery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The preferred embodiments of the present disclosure are described below in conjunction with the accompanying drawings, in which:
[0022] Figure 1 A flow chart of the preparation of the TOPcon battery provided in the present disclosure;
[0023] Figures 2 to 5 A cross-sectional structure diagram of a TOPcon battery provided in the present disclosure during the preparation process;
[0024] Figure 6 This is a cross-sectional structural diagram of the TOPcon battery provided in the present invention.
[0025] Description of reference numerals:
[0026] 1. substrate; 11. doping layer; 2. tunneling oxide layer; 3. polysilicon layer; 4. passivation layer; 5. first anti-reflection layer; 6. second anti-reflection layer; 71. first electrode; 72. second electrode; 10. first groove; 20. second groove. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present disclosure are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present disclosure and are not intended to limit the protection scope of the present disclosure.
[0028] It should be noted that in the description of the present disclosure, the terms "upper", "lower", "left", "right", "inner", "outer" and the like indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings, which are only for the convenience of description, and do not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present disclosure. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0029] In order to solve the problem that it is difficult to maintain or improve the fill factor while increasing the open circuit voltage of a TOPcon battery, the present disclosure provides a method for preparing a TOPcon battery, such as Figure 1 As shown, the preparation method includes: providing a battery substrate, the battery substrate includes a substrate and a doping layer, a passivation layer and a first anti-reflection layer formed in sequence on the first side of the substrate; forming a first groove, the first groove extending from the surface of the first anti-reflection layer to the first anti-reflection layer or the passivation layer; printing metal paste in the first groove; heating and sintering the metal paste so that the paste passes through the passivation layer and forms an ohmic contact with the doping layer. .
[0030] Figures 2 to 5 This is a cross-sectional structural diagram of the TOPcon battery provided in the present invention during the preparation process. Figure 6 This is a cross-sectional structural diagram of the TOPcon battery provided in the present invention.
[0031] The preparation method of the TOPcon battery provided in the present disclosure is specifically as follows:
[0032] S1. Provide a substrate 1, wherein the substrate 1 is of a first doping type.
[0033] S2. Texturing is performed on the first side surface of the substrate 1 and the second side surface opposite to the first side surface, and a pyramid-like structure is formed on the first side surface and the second side surface of the substrate 1, thereby reducing the reflection of incident light, thereby improving the short-circuit current interruption of the battery, and further improving the photoelectric conversion efficiency of the battery. Among them, the first side surface of the substrate 1 is the light-facing surface, and the second side surface of the substrate 1 is the backlight surface. After the first side surface of the substrate 1 is texturing, the film layers formed on the first side surface have the same velvet structure as the first side surface.
[0034] As a specific example, the substrate 1 is put into a texturing liquid for texturing. The mass ratio of the components in the texturing liquid is H2O:KOH:additive=354:5.5:2, and the main components of the additive include: surfactant, nucleating agent, dispersant, catalyst and defoaming agent. The texturing temperature is 80°C and the texturing time is 400 seconds.
[0035] S3. Doping is performed on the first side of the substrate 1 to form a doping layer 11 of the second doping type on the first side. For example, when the substrate 1 is N-type doped, the doping type of the doping layer 11 is P-type doping, thereby forming a PN junction. As a specific example, the N-type single crystal silicon substrate 1 is placed in a boron diffusion furnace tube for a boron diffusion process, and the process temperature of the boron diffusion is 900°C to 1100°C. Boron sources such as trimethyl borate, boron tribromide, and boron trichloride can be used for boron diffusion. In the process of forming the boron doping layer (i.e., the doping layer 11) on the first side, a BSG (borosilicate glass) layer will naturally form under the action of oxygen.
[0036] It should be noted that the present disclosure does not impose specific restrictions on the boron source, process temperature, diffusion depth, etc. of the boron diffusion or phosphorus diffusion process. Personnel in this field can design according to actual needs, and the above limitations are only some specific examples.
[0037] S4. Remove the boron diffusion layer that has expanded on the second side, while retaining the BSG layer on the first side.
[0038] S5. A tunneling oxide layer 2 and a doped polysilicon layer 3 are sequentially formed on the second side of the substrate 1. The tunneling oxide layer 2 can saturate the dangling bonds on the surface of the substrate 1, reduce the interface defect state density on the second side of the substrate 1, and thus reduce the recombination center on the second side of the substrate 1, thereby reducing the recombination rate of carriers, and ultimately increasing the open circuit voltage of the solar cell and improving the photoelectric conversion efficiency of the solar cell. The material of the tunneling oxide layer 2 is silicon oxide. The doping type of the polysilicon layer 3 is the same as the doping type of the substrate 1.
[0039] For example, the tunnel oxide layer 2 is formed by chemical vapor deposition.
[0040] For example, the polysilicon layer 3 can be formed by chemical vapor deposition. In addition, a single crystal silicon layer can be formed first, and then the doped polysilicon layer 3 can be formed by doping and high-temperature annealing. As a specific example, when chemical vapor deposition is used, raw material gas (such as SiCl4, SiHCl3 or SiH4), doping gas (such as PH3) and hydrogen can be introduced, and after chemical reaction, the doped polysilicon layer 3 is grown on the second side. Therefore, the polysilicon layer 3 is generally doped with hydrogen atoms, so that the polysilicon layer 3 also has a certain passivation effect.
[0041] For example, the thickness of the polysilicon layer 3 is 45 nm to 85 nm, preferably 50 nm to 80 nm.
[0042] S6, removing the polysilicon layer 3 disposed on the first side and edge of the substrate 1.
[0043] S7, forming a passivation layer 4 on the side of the doping layer 11 away from the substrate 1, forming Figure 2 The structure shown.
[0044] As a specific example, the material of the passivation layer 4 is aluminum oxide, which is formed by plasma enhanced chemical vapor deposition. For example, a mixed gas of trimethylaluminum and oxygen or nitrogen oxide (i.e., a mixed gas of trimethylaluminum and oxygen, or a mixed gas of trimethylaluminum and nitrogen oxide) is introduced, and the reaction temperature is between 250° C. and 350° C., thereby forming a passivation layer 4 of aluminum oxide. The thickness of the passivation layer 4 is 4 nm to 6.5 nm, preferably 4.5 nm to 6 nm.
[0045] S8, forming a first anti-reflection layer 5 on the passivation layer 4, and forming a second anti-reflection layer 6 on the polysilicon layer 3, so as to form Figure 3 The first anti-reflection layer 5 and the second anti-reflection layer 6 can reflect the light entering the solar cell, so that more sunlight is absorbed by the solar cell, thereby improving the short-circuit current interruption of the cell and further improving the photoelectric conversion efficiency of the cell.
[0046] As a specific example, the material of the first anti-reflection layer 5 and the second anti-reflection layer 6 is silicon nitride, and is formed by plasma enhanced chemical vapor deposition. For example, a mixed gas of SiH4 and NH3 is introduced, and the reaction temperature is between 300° C. and 550° C., so as to form the first anti-reflection layer 5 and the second anti-reflection layer 6 of silicon nitride. The thickness of the first anti-reflection layer 5 and the second anti-reflection layer 6 are both 70nm to 100nm.
[0047] In some examples, the semiconductor structure manufactured by steps S1 to S8 can be used as a battery substrate for performing step S9 and subsequent steps.
[0048] S9, forming a first electrode 71, wherein the first electrode 71 forms an ohmic contact with the doping layer 11 after passing through the first anti-reflection layer 5 and the passivation layer 4.
[0049] In the examples of the present disclosure, Figures 4 to 6 As shown, the process of forming the first electrode 71 is as follows:
[0050] S91, such as Figure 4 As shown, firstly, a first groove 10 is formed, and the first groove 10 extends from the surface of the first anti-reflection layer 5 to the inside of the first anti-reflection layer 5 or the passivation layer 4. As a specific example, the first groove 10 extends to the inside of the passivation layer 4.
[0051] Specifically, laser etching is used to form a marking point on the first anti-reflection layer 5 and at a position corresponding to the first electrode 71, and the first anti-reflection layer 5 and a part of the passivation layer 4 at the position corresponding to the first electrode 71 are etched away by laser (i.e., the first groove 10 extends into the passivation layer 4), and a thinner passivation layer 4 (i.e., the passivation layer area exposed by the first groove 10) is retained at the position corresponding to the first electrode 71, and the thickness thereof is 1nm to 2.5nm, preferably 2nm. For example, the parameters of the laser for etching include: a wavelength of 355nm, a power of 5W, a pulse frequency of 1KHz to 40KHz, and a scanning speed of 30nm / s to 100mm / s.
[0052] S92, printing metal paste (such as Figure 5 As shown), the metal paste is then heated and sintered, so that the metal paste corrodes the passivation layer 4 at high temperature and forms an ohmic contact with the doping layer 11 (as shown Figure 6 The peak temperature of the heating sintering is 600°C to 700°C, which is 100°C to 150°C lower than the peak temperature of 750°C to 800°C in the known technology.
[0053] S93 , the metal paste is cooled to form a first electrode 71 .
[0054] By opening the first groove 10, the thickness of the passivation layer 4 corroded by the metal slurry during the heating and sintering process can be reduced, so as to ensure that when the sintering temperature is reduced, the metal slurry located in the first groove 10 can also corrode the remaining passivation layer 4, thereby forming a good ohmic contact with the doping layer 11, so as to maintain the filling factor of the battery. In addition, after the sintering temperature is reduced, the escape of hydrogen atoms doped in each film layer (such as the polysilicon layer 3, the passivation layer 4, the first anti-reflection layer 5 and the second anti-reflection layer 6) in the battery can be effectively reduced to maintain the passivation effect of each film layer, thereby improving the open circuit voltage of the battery; at the same time, after the sintering temperature is reduced, the degree of damage to the passivation layer 4 by the metal slurry is reduced, and the consistency of the corrosion thickness of the passivation layer 4 by the metal slurry in all directions is high, so that the contact site between the metal slurry and the doping layer 11 is more uniform, which helps to maintain the filling factor of the battery.
[0055] In some examples, the metal paste uses low-corrosive silver paste to control the rate at which the metal paste corrodes the passivation layer 4 and the doping layer 11, to prevent the metal paste from corroding and penetrating the doping layer 11 and contacting the substrate 1, and to reduce the damage of the silver paste to the passivation layer 4 in the lateral direction. The main components of the silver paste include silver powder, glass powder, organic carrier and inorganic additives. The corrosiveness of the silver paste can be effectively reduced by reducing the ratio of the glass powder. For example, the ratio of the silver paste by weight percentage is: 90% to 95% silver powder, 0.2% to 0.3% glass powder, 1% to 3% organic carrier and 0% to 1% inorganic additive. For example, glass powder includes SiO2, B2O3, TiO2 and PbO, organic carriers include organic solvents (such as alcohol ester, diethylene glycol butyl ether, etc.), organic resins (such as acrylic resin, hydroxyethyl cellulose, polyvinyl butyral resin) and additives (such as polyamide wax, hydrogenated castor oil, dimethyl silicone oil), inorganic additives include composite additives (such as silver oxide, silver silicate, silver borate, silver selenate one or more) and other additives (such as aluminum powder, lead powder, zinc powder, silicon-magnesium alloy powder, boron powder, silicon powder, boronized silicon powder, silicon nitride, boron nitride, aluminum boride, zinc oxide powder, bismuth oxide powder, silicon dioxide powder one or more).
[0056] In some examples, the process of forming the first electrode 71 further includes:
[0057] S94, laser-assisted sintering of the metal slurry. It should be noted that step S94 is performed after step S93.
[0058] As a specific example, a bias voltage of 10V to 40V is applied between the metal paste and the second anti-reflection layer 6, and a laser with a wavelength of 500nm to 1200nm and a power of 10% to 80% is used to scan the metal paste in a line scanning manner, with a scanning speed of 30nm / s to 100mm / s and a scanning time of 0.5s to 1s. Among them, the spot diameter of the laser is 50μm to 300μm, and the shape is square or circular, etc. The metal paste is heated by laser, and the heat of the metal paste is concentrated and the heat dissipation is fast, which will not cause a large temperature rise in the remaining film layers in the battery, and therefore will not cause the battery to lose open circuit voltage; and under the action of the bias, silver ions can be effectively adsorbed on the doping layer 11, thereby improving the ohmic contact effect between the metal paste and the doping layer 11, thereby improving the filling factor of the battery, and achieving the purpose of improving battery efficiency.
[0059] S10 , forming a second electrode 72 , wherein the second electrode 72 passes through the second anti-reflection layer 6 and forms an ohmic contact with the polysilicon layer 3 .
[0060] In the examples of the present disclosure, Figures 4 to 6 As shown, the process of forming the second electrode 72 is as follows:
[0061] S101, forming a second groove 20. The second groove 20 extends from the surface of the second anti-reflection layer 6 to the inside of the second anti-reflection layer 6 or the polysilicon layer 3 (eg Figure 4 shown).
[0062] As a specific example, laser etching is used to form a marking point on the second anti-reflection layer 6 and at a position corresponding to the second electrode 72, and the second anti-reflection layer 6 and a portion of the polysilicon layer 3 at a position corresponding to the second electrode 72 are etched away by laser (that is, the second groove 20 extends into the polysilicon layer 3), and a thinner polysilicon layer 3 is retained at a position corresponding to the second electrode 72. The depth of the second groove 20 in the polysilicon layer 3 is 15nm to 35nm, preferably 20nm to 30nm.
[0063] For example, the parameters of the laser used for etching include: wavelength of 355 nm, power of 5 W, pulse frequency of 1 KHz to 40 KHz, and scanning speed of 30 nm / s to 100 mm / s.
[0064] S102, printing metal paste (such as Figure 5 As shown), the metal paste is then heated and sintered, wherein the heating and sintering specifically adopts heating and sintering to form a silicon-metal alloy between the metal paste and the polysilicon, thereby improving the ohmic contact effect between the metal paste and the polysilicon layer 3, thereby improving the filling factor of the battery, and ultimately improving the efficiency of the battery. After heating and sintering, the metal paste extends into the polysilicon layer 3 to avoid damaging the tunneling oxide layer 2 and reducing the open circuit voltage of the battery.
[0065] The peak temperature of the heating sintering is 600°C to 700°C, which is 100°C to 150°C lower than the peak temperature of 750°C to 800°C in the known technology.
[0066] S103 , the metal paste is cooled to form a second electrode 72 .
[0067] By opening the second groove 20, the thickness of the second anti-reflection layer 6 corroded by the metal slurry can be reduced during the heating and sintering process (when the bottom of the second groove 20 is located in the polysilicon layer 3, the metal slurry does not need to corrode the second anti-reflection layer 6 along the thickness direction of the battery). In this way, even when the sintering temperature is lowered, it is possible to ensure that the metal slurry forms a good ohmic contact with the polysilicon layer 3.
[0068] In addition, as the sintering temperature decreases, the rate at which the metal slurry corrodes the polysilicon layer 3 will also decrease, which helps control the depth of the metal slurry corroding the polysilicon layer 3. Therefore, in the process of forming the polysilicon layer 3, the polysilicon layer 3 can be thinned to reduce the parasitic absorption of the battery. In the case where the polysilicon layer 3 is thin, the metal slurry is not easy to corrode and penetrate the polysilicon layer 3.
[0069] In addition, after the sintering temperature is reduced, the escape of hydrogen atoms doped in each film layer in the battery (such as the polysilicon layer 3, the passivation layer 4, the first anti-reflection layer 5 and the second anti-reflection layer 6) can be effectively reduced to maintain the passivation effect of each film layer, thereby improving the open circuit voltage of the battery.
[0070] In some examples, the metal paste uses a low-corrosive silver paste to control the rate at which the metal paste corrodes the second anti-reflection layer 6 and the polysilicon layer 3, thereby preventing the metal paste from corroding and penetrating the polysilicon layer and damaging the tunnel oxide layer 2. The low-corrosive silver paste printed on the second anti-reflection layer 6 can have the same ratio as the low-corrosive silver paste printed on the first anti-reflection layer 5.
[0071] In some examples, the process of forming the second electrode 72 further includes:
[0072] S104, laser-assisted sintering of the metal slurry. The specific steps of laser-assisted sintering are similar to those in step S94, except that a bias voltage is applied between the metal slurry and the first anti-reflection layer. After the metal slurry is subjected to secondary sintering by laser sintering, the temperature rise of the metal slurry is instantaneous, and the heat dissipation is fast, which will not cause a large temperature rise in the remaining film layers in the battery, and therefore will not cause the battery to lose open-circuit voltage; and under the action of the bias voltage, the silver ions can be effectively adsorbed on the polysilicon layer 3, thereby improving the ohmic contact effect between the metal slurry and the polysilicon layer 3, thereby improving the fill factor of the battery and achieving the purpose of improving the battery efficiency.
[0073] It should be noted that step S104 is performed after step S103.
[0074] In some examples, heating and sintering of the metal paste printed on the first side and the second side of the substrate 1 can be performed in the same process step. After heating and sintering of the metal paste printed on the first side and the second side of the substrate 1, the cell can be subjected to light injection treatment.
[0075] In summary, the preparation method of the TOPcon battery provided in the present disclosure has at least the following advantages:
[0076] (1) By lowering the temperature for heating and sintering the metal paste printed on the first side and / or the second side of the substrate 1, the escape of hydrogen atoms doped in each film layer (such as the polysilicon layer 3, the passivation layer 4, the first anti-reflection layer 5 and the second anti-reflection layer 6) in the battery can be effectively reduced to maintain the passivation effect of each film layer, thereby improving the open circuit voltage of the battery.
[0077] (2) By lowering the temperature for heating and sintering the metal paste printed on the first side of the substrate 1, the degree of damage to the passivation layer 4 caused by the metal paste can be reduced, which helps to improve the open circuit voltage of the battery; in addition, the corrosion thickness of the passivation layer 4 by the metal paste in all directions is more consistent, making the contact points between the metal paste and the doping layer 11 more uniform, which helps to maintain the fill factor of the battery.
[0078] (3) By opening the first groove 10, the thickness of the passivation layer 4 corroded by the metal paste during the heating and sintering process can be reduced. When the sintering temperature is lowered, the metal paste in the first groove 10 can also corrode the remaining passivation layer 4, thereby forming a good ohmic contact with the doping layer 11, thereby maintaining the fill factor of the battery.
[0079] (4) By opening the second groove 20, the thickness of the second anti-reflection layer 6 corroded by the metal slurry can be reduced during the heating and sintering process. When the sintering temperature is lowered, it can also be ensured that the metal slurry forms a good ohmic contact with the polysilicon layer 3, thereby maintaining the fill factor of the battery.
[0080] (5) By lowering the temperature for heating and sintering the metal paste printed on the second side of the substrate 1, the rate at which the metal paste corrodes the polysilicon layer 3 is reduced, which helps to control the depth of the metal paste corroding the polysilicon layer 3; therefore, in the process of forming the polysilicon layer 3, the polysilicon layer 3 can be thinned to reduce the parasitic absorption of the battery. When the polysilicon layer 3 is thin, the metal paste is not easy to corrode and penetrate the polysilicon layer 3.
[0081] (6) Printing a low-corrosive silver paste on the first side of the substrate 1 helps control the corrosion rate of the silver paste on the passivation layer 4 and reduces the possibility of the silver paste corroding through the passivation layer and contacting the substrate.
[0082] (7) Printing a low-corrosive silver paste on the second side of the substrate 1 helps control the rate at which the silver paste corrodes the polysilicon layer 3 and reduces the possibility of the silver paste corroding through the polysilicon layer 3 and damaging the tunnel oxide layer.
[0083] (8) After the metal paste is heated and sintered, laser-assisted sintering is used for secondary sintering to improve the ohmic contact effect between the metal paste and the passivation layer 4 and / or the polysilicon layer 3 without causing the battery to lose open-circuit voltage, thereby improving the fill factor of the battery and achieving the purpose of improving the battery efficiency.
[0084] The present disclosure also provides a TOPcon battery, which is prepared using the above preparation method.
[0085] There are a few points to note:
[0086] (1) The drawings of the embodiments of the present disclosure only relate to the structures related to the embodiments of the present disclosure, and other structures may refer to the general design.
[0087] (2) For the sake of clarity, in the drawings used to describe the embodiments of the present disclosure, the thickness of layers or regions is enlarged or reduced, that is, these drawings are not drawn according to the actual scale.
[0088] (3) In the absence of conflict, the embodiments of the present disclosure and the features therein may be combined with each other to obtain new embodiments.
[0089] So far, the technical solutions of the present disclosure have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present disclosure is obviously not limited to these specific embodiments. Without departing from the principles of the present disclosure, those skilled in the art may make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present disclosure.
Claims
1. A method for preparing a TOPcon battery, characterized in that: include: Providing a battery substrate, the battery substrate comprising a substrate and a doping layer, a passivation layer and a first anti-reflection layer sequentially formed on a first side of the substrate; forming a first groove, wherein the first groove extends from the surface of the first anti-reflection layer into the first anti-reflection layer or into the passivation layer; printing metal paste in the first groove; The metal paste is heated and sintered so that the metal paste passes through the passivation layer and forms an ohmic contact with the doping layer.
2. The method for preparing a TOPcon battery according to claim 1, characterized in that: The first groove extends into the passivation layer, and the thickness of the passivation layer region exposed by the first groove is 1 nm to 2.5 nm.
3. The method for preparing a TOPcon battery according to claim 1, characterized in that: The peak temperature of the heating sintering is 600°C to 700°C.
4. The method for preparing a TOPcon battery according to claim 1, characterized in that: The metal paste is silver paste, and the proportion of the silver paste by weight percentage is: 90% to 95% silver powder, 0.2% to 0.3% glass powder, 1% to 3% organic carrier and 0% to 1% inorganic additive.
5. The method for preparing a TOPcon battery according to claim 1, characterized in that: The preparation method further comprises: After the metal slurry is heated and sintered, the metal slurry is subjected to laser-assisted sintering.
6. The method for preparing a TOPcon battery according to claim 5, characterized in that: The laser assisted sintering comprises: applying a bias voltage of 10V to 40V between the metal paste and the second side of the substrate; The wavelength of the scanning laser is 500nm to 1200nm, the scanning speed is 30nm / s to 100mm / s, and the scanning time is 0.5s to 1s.
7. The method for preparing a TOPcon battery according to claim 1, characterized in that: The thickness of the passivation layer is 4 nm to 6.5 nm.
8. The method for preparing a TOPcon battery according to claim 1, characterized in that: The thickness of the first anti-reflection layer is 70 nm to 100 nm.
9. The method for preparing a TOPcon battery according to any one of claims 1 to 8, characterized in that: The preparation method further comprises: A tunneling oxide layer, a polysilicon layer and a second anti-reflection layer are sequentially formed on the second side of the substrate.
10. The method for preparing a TOPcon battery according to claim 1, characterized in that: The preparation method further comprises: Before forming the doping layer, texturing is performed on the first side of the substrate.
Citation Information
Cited By
Solar cell and preparation method thereof, laminated cell and photovoltaic module
CN120456670A